2022
DOI: 10.3390/e24121794
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Design Method for Highway Adjacent Tunnel and Exit Connection Section Length Based on Entropy Method

Abstract: With the continuous construction of transportation infrastructure, intersection nodes have been increasing rapidly, bringing growing numbers of tunnel- and exit-adjacent sections (TEAS) in mountain expressways in China. With the complex variation in the surrounding environment, drivers always face congestion and confusion on tunnel and the exit connecting sections (TECS) without adequate length, meanwhile excessively long TECS create detours. To better provide a sustainable design strategy for TEAS, based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Some scholars have given ramp spacing recommendations for two different ramp combinations: "entrance-exit" and "exit-exit" [31]. Through theoretical derivation and simulation, Liu proposed the spacing between tunnel exits and interchange exits according to varying traffic volumes and diverging rates and comprehensively evaluated the traffic efficiency and pollutant emissions of different schemes based on entropy [32]. Based on a data envelopment analysis combined with a hierarchical analysis, the optimal spacing is proposed for the four ramp combination types of exit and entrance [33].…”
Section: Small Spacing Interchange Improvement Methodsmentioning
confidence: 99%
“…Some scholars have given ramp spacing recommendations for two different ramp combinations: "entrance-exit" and "exit-exit" [31]. Through theoretical derivation and simulation, Liu proposed the spacing between tunnel exits and interchange exits according to varying traffic volumes and diverging rates and comprehensively evaluated the traffic efficiency and pollutant emissions of different schemes based on entropy [32]. Based on a data envelopment analysis combined with a hierarchical analysis, the optimal spacing is proposed for the four ramp combination types of exit and entrance [33].…”
Section: Small Spacing Interchange Improvement Methodsmentioning
confidence: 99%
“…Configuration 1 is the original U-turn design, where vehicles complete a U-turn before the stop line for the intersection The prerequisite for accurately replicating real traffic conditions using VISSIM simulation software requires the input of specific parameters. Based on the driving habits of Chinese drivers and in connection with available research [49][50][51][52], some of these parameters are specified as follows:…”
Section: Preparation For Establishing the Vissim Modelmentioning
confidence: 99%
“…In the field of transportation, numerous studies have shown the reliable, effective, and economic advantages of using VISSIM numerical simulation [25,26]. To ensure reliability and realism, it is essential to incorporate real traffic data in the development of the simulation model and the calibration of parameters to recreate specific traffic scenarios [27]. Furthermore, benefiting from the emergence of target detection algorithms, the use of unmanned aerial vehicles (UAV) in data measurement can achieve better efficiency compared to conventional radar measurements [28].…”
Section: Introductionmentioning
confidence: 99%
“…The core of the CE method, which aims to assign weights to indicators with different amounts of information, has been successfully applied in various fields, including economics [32], medicine [33], environment [34], and transportation [27]. Among those, the entropy method, which determines the weights based on the variability of indicators, is the most frequently used type of method [35].…”
Section: Introductionmentioning
confidence: 99%